Phase transitions and magnetization of the mixed-spin Ising–Heisenberg double sawtooth frustrated ladder. (28th March 2018) - Arian Zad, Hamid; Ananikian, Nerses
Abstract: The mixed spin-(1, 1/2) Ising–Heisenberg double sawtooth ladder containing a mixture of both spin-1 and spin-1/2 nodal atoms, and the spin-1/2 interstitial dimers are approximately solved by the transfer-matrix method. Here, we study in detail the ground-state phase diagrams, also influences of the bilinear exchange coupling on the rungs and cyclic four-spin exchange interaction in square plaquette of each block on the magnetization and magnetic susceptibility of the suggested ladder at low temperature. Such a double sawtooth ladder may be found in a Shastry-Sutherland lattice-type. In spite of the spin ordering of odd and even blocks being different from each other, due to the commutation relation between all different block Hamiltonians, phase diagrams, magnetization behavior and thermodynamic properties of the model are the same for odd and even blocks. We show that at low temperature, both exchange couplings can change the quality and quantity of the magnetization plateaus versus the magnetic field changes. Specially, we find a new magnetization plateau M / M s = 5 / 6 for this model. Besides, we examine the magnetic susceptibility and specific heat of the model in detail. It is proven that behaviors of the magnetization and the magnetic susceptibility coincide at low temperature. The specific heat displays diverse temperature dependencies, which include a Schottky-type peak at a special temperature interval. We observe that with increase of the bilinear exchange coupling on the rungs, second peak temperature dependence grows.